PolyMeCo-An integrated environment for polygonal mesh analysis and comparison - Silva, S. (2009)
Polygonal meshes are used in several application areas to model different objects and structures. Depending on the application, mesh models sometimes have to be processed to, for instance, reduce their complexity (mesh simplification). Such operations introduce differences regarding the original mesh, whose evaluation is of paramount importance when choosing the processing methods to be applied for a particular purpose. Although some mesh analysis and comparison tools are described in the literature, little attention has been given to the way mesh features and mesh comparison results can be visualized. Moreover, particular functionalities have to be made available to enable systematic use and proper data analysis and exploration. PolyMeCo-a tool for polygonal mesh analysis and comparison-was designed and developed taking the above objectives into account. It enhances the way users analyze features and compare meshes by providing an integrated environment where various mesh quality measures and several visualization options are available and can be used in a coordinated way, thus leading to greater insight into the visualized data.